Keeping a Keen Eye on Unsanctioned Aggression in Contact Sports in China: Do Personal, Aggressive and Moral Factors Count in it? - Zhengchun Hu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This research reviews the factors related to the socio-cognitive self-regulatory processes influential on the unsanctioned aggression which may have received only limited attention in sports psychology; however, the present study has been designed with a view to rectify this gap. The primary purpose of the present study is to evaluate the unsanctioned aggression prevalent in contact sports. For this purpose the self-enhancement values, resistive self-regulatory efficacy and the self-transcendence values are considered as personal factors where moral disengagement and aggressive provocative tendency have been considered as well. The study adopts a quantitative design and online questionnaires have been used to generate a sample from 334 respondents. The data has been collected from people involved in different contact sports in China. Structural equation modelling is used for the evaluation of the variable relationships. The influence of the personal self-transcendence is found to lead to an increase in unsanctioned aggression in the contact sports players where the moral disengagement and aggressive provocative tendency effectively mediated the association. The results show that the self-transcendence, moral disengagement and aggressive provocative tendency govern the unsanctioned aggression of the contact sports players of China. The study produces a number of key practical, theoretical and policy-oriented implications. The present carries a number of design limitations that may be overcome in the work of future researchers. The findings of the study can be used by coaches, athletes, sports psychologists and decision-makers for the purpose of sports coaching as well as to lower the level of aggressiveness in contact sport players. By and large, the key limitation of the study is that it only considers the contact sports players in the context of China.